Synthesis of Some Imine, From Pyrazole -1- Carbaldehyde Compound - Natiq Ahmad; YASSIR AL-JAWAHERI (College of Education for Pure Sciences, 2021)
In this paper the synthesis of  N[(1E)-1- ( 3,5.- disubstituted phenyl -4,5-dihydro-1H- pyrazol-1- yl) ethylidene or methylidene] substituted aniline [13-15] [17-19] and 1,1-{benzene- 1,4- or -1,3- diylbis [nitrilo (E) methylylidene]} bis( 4,5- dihydro -1H- pyrazole -3,5- disubstituted phenyl) [16,20] is reported. Substituted acetophenone was treated with substituted benzaldehyde to give chalcones ((2E)-1,3- disubstituted phenyl prop-2-ene-1- one) [1-4], the chalcones was treated with hydrazine hydrate in the presence of formic or acetic acid ethanol to give 1-(3,5.-disubstituted phenyl-4,5- dihydro-1H- pyrazol-1- yl) methanol or ethanone [5-12], then this products changed to imines through reaction with substituted aromatic aniline and sodium hydroxide in ethanol to give the substituted pyrazoles. Also the substituted compounds [5-12] were converted to 1-{(1E)-1-[2-(2,4-dinitrophenyl) hydrazinylidene] methyl or ethyl} - 4,5- dihydro -1H- pyrazole-3,5-disubstituted phenyl [21-28] by reaction with 2,4-dinitrophenyl hydrazine in ethanol. The synthetic compound's structure. confirmed by IR., UV. Spectra and. physical method.